(untitled) (REVISTA NERA, 2012)
The paper analyses in the Latin American context the dynamics associated with the capitalist development process, namely, the productive and social transformation of an agrarian society and economy into a modern industrial capitalist system. This process implies a process of primitive accumulation (separation of the direct producers from the land) and the proletarianization of the peasantry. The project of development with international cooperation was designed and serves to assist the dispossessed rural poor in adjusting to the forces of progressive change released in the process, rather than resisting them. The paper also deals with the resistance of the rural landless workers and other elements of the peasantry against the neoliberal model of capitalist development that threatens the viability and sustainability of their livelihoods.